Netherlands : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This Selected Issues paper on the Kingdom of the Netherlands reviews the cyclical position of the Dutch economy, and provides a comparison of different estimates of the nonaccelerating inflation rate of unemployment and the potential output. The study analyzes the adjustment mechanisms embedded in the central projections of a number of forecasters, and investigates the sensitivity of the outlook to upside demand risks using macroeconometric models. The paper also evaluates the effect of changes in the monetary and fiscal policies, key features of labor, and asset markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet